Temporal ordering of motivational quality and athlete burnout in elite sport - Lonsdale, C.; Hodge, K. (Medicine & Science in Sports & Exercise, 2011)
Introduction: Using self-determination theory as the theoretical framework, we conducted a longitudinal investigation of the relationships between motivation and athlete burnout. We tested four hypotheses: H0: low self-determination (SD) does not precede burnout, and burnout does not precede low SD; H1: low SD precedes burnout; H2: burnout precedes low SD; and H3: burnout and motivation have a reciprocal relationship.